Scope of practice of Japanese primary care physicians and its associated factors: a cross-sectional study - Toshiyuki Ojima; Machiko Inoue; Mieko Nakamura; Tomoya Higuchi (Family Medicine and Community Health)
Objective The scope of practice (SOP) of primary care physicians (PCPs) has been narrowing, with declining comprehensiveness leading to fragmented care. Identifying SOP-associated factors can help improve comprehensiveness. This study aimed to describe the SOP of PCPs working in clinics and to identify SOP-associated factors.Design A cross-sectional study using a self-administered questionnaire.Setting Shizuoka, Japan.Participants PCPs working in clinics offering internal medicine.Main outcome measures The total number of services provided, covering 109 items, was categorised into 8 clinical areas, 78 clinical activities and 23 procedures.Results Questionnaires were mailed to 1191 clinics, and 389 valid responses were included in the analysis. Of the 389 physicians, 254 (65.3%) were internal medicine specialists, and 382 (98.2%) worked in their own private clinics. The mean number of services provided was 60.4±17.4. Clinical activities were provided less frequently in the areas of paediatric and adolescent care, women’s health, home healthcare, palliative care and mental health. Physician-related factors were more significantly associated with SOP than practice or environmental factors. Preference for broad practice was the strongest factor associated with a broader SOP, followed by completion of the Japan Medical Association (JMA) primary care training programme and rotational training experience. Additionally, younger physician age, rural practice experience, surgical specialisation, a larger number of physicians in the clinic, higher patient volume and a more rural setting were associated with broader SOP.Conclusion Physician preference regarding SOP, completion of the JMA primary care training programme and rotational training are key factors influencing SOP. These findings suggest that postgraduate clinical training with a broad scope not limited to internal medicine and continuing medical education after establishing a private clinic, particularly for physicians who prefer broad practice, may be important in expanding the SOP of PCPs.